2012
DOI: 10.1002/jcu.21918
|View full text |Cite
|
Sign up to set email alerts
|

Detailed ultrasound screening in the second trimester: Pictorial essay of normal fetal anatomy

Abstract: Today, ultrasound is the main diagnostic tool in the prenatal detection of congenital abnormalities. Therefore, ultrasound examination should be offered to all pregnant women. A detailed sonographic examination of the fetus is usually performed between 18 and 22 weeks of pregnancy. The accurate recognition of normal fetal anatomy is very important for the detection of both minor and major defects. The purpose of this pictorial essay is to show fetal anatomic structures, which have to be examined between the 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…This involves measuring the cerebellar diameter in the transcerebellar plane, which is a plane passing through the thalamus and cavum septum pellucidum. In this section, it is possible to identify the occipital horns of the lateral ventricles, the thalami, the interhemispheric fissure, and the cerebellum [ 38 ], which, in cross-section, appears as a butterfly-shaped structure, with the vermis recognizable as being slightly more echogenic than the two cerebellar hemispheres [ 27 ]. Among the coronal planes, the only one that can be acquired via the posterior fontanelle is the transcerebellar plane [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This involves measuring the cerebellar diameter in the transcerebellar plane, which is a plane passing through the thalamus and cavum septum pellucidum. In this section, it is possible to identify the occipital horns of the lateral ventricles, the thalami, the interhemispheric fissure, and the cerebellum [ 38 ], which, in cross-section, appears as a butterfly-shaped structure, with the vermis recognizable as being slightly more echogenic than the two cerebellar hemispheres [ 27 ]. Among the coronal planes, the only one that can be acquired via the posterior fontanelle is the transcerebellar plane [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers 33 suggest that 3D/4D ultrasound of the fetal face does not aid diagnosis; however, others 18,34 have concluded that during routine screening when using 2D imaging techniques, the exa miner needs to image several planes and hence making the examination longer than with 3D/4D scan ning. Specifically, if using 2D imaging techniques to establish the presence of facial abnormalities of lip and nose morphology (facial dysmorphology) both the midsagittal plane and the anterior 'nose-mouth' coronal plane need to be visualized.…”
Section: Use Of Ultrasound Images Can We Use Fetal Facial Movements Fmentioning
confidence: 99%